Tratamento da retocolite ulcerativa: Atualização clínica - Teixeira, Fabio Vieira [UNESP]; Hosne, Rogerio Saad [UNESP]; Sobrado, Carlos Walter (Thieme, 2015)
The objective of this study was to evaluate the consensus of expert societies and published guidelines on the management of ulcerative colitis, and to compare with the experience of the authors, in order to standardize procedures that would help the reasoning and decision- making process of the physician. A search was performed in scientiﬁc literature, speciﬁcally in electronic databases: Medline/Pubmed, SciELO, EMBASE and Cochrane, and the following descriptors were used: ulcerative colitis, acute colitis, clinical treatment, surgery and ran- domized trial. It can be concluded that the goals of therapy in ulcerative colitis are clinical and endoscopic remission, deep, sustained remission without corticosteroids, prevention of hospitalizations and surgeries, and improved quality of life. The surgical indications are reserved for selected cases, ranging from medical intractability, complications (severe refractory acute colitis, toxic megacolon, perforation and hemorrhage) and malignancy. Information in this review article must be submitted to evaluation and criticism of the spe- cialist responsible for the conduct to be followed, in the face of his/her reality and the clinical status of each patient. The degree of recommendation and strength of evidence were based using the GRADE sys- tem (The Grades of Recommendation, Assessment, Development, and Evaluation) described below: 1. A: Experimental or observational studies of higher consistency. 2. B: Experimental or observational studies of lower consistency. 3. C: Case reports (non-controlled studies). 4. D: Opinion without critical evaluation, based on consensus, physiological studies or animal models.
Management of ulcerative colitis: A clinical update
Keywords: Acute colitis; Clinical treatment; Complications; Surgery; Ulcerative colitis